Role of capsaicin-sensitive nerves in gastric and hepatic injury induced by cold-restraint stress - (:unkn) unknown (KLUWER ACADEMIC/PLENUM PUBL, 2000)
The role of capsaicin-sensitive afferent fibers on cold-restraint stress-induced gastric and hepatic injury was examined at the macroscopic and ultrastructural levels. Wistar albino rats were treated with capsaicin either locally (intragastric, perivagal, and periceliac) or systemically (neonatal, intraperitoneal). Perineural and neonatal treatment with capsaicin was used to denervate afferent fibers, while intragastric capsaicin treatment would have activated mucosal afferent fibers just before the stress exposure. Capsaicin decreased significantly the formation of macroscopic gastric lesions caused by stress in all treatment groups. At the electron microscopic level, however, denervation of vagal afferent fibers with capsaicin was most effective in prevention of cellular injury in gastric mucosa. In the liver, systemic denervation of afferent fibers completely inhibited stress-induced cellular damage, while denervation of afferentt fibers in vagus and splanchnic nerve was partially effective. Central neural pathways sensitive to capsaicin may mediate formation of both gastric and hepatic injury resulting from stress.
Keywords: capsaicin; stress; liver; stomach; lipid peroxidation; glutathione; GENE-RELATED PEPTIDE; AFFERENT NEURONS; ACID SECRETION; INTRAGASTRIC CAPSAICIN; SENSORY NEURONS; MOTOR FUNCTION; RAT STOMACH; BLOOD-FLOW; PROTECTION; TACHYKININS